Aplikasi Konsep Desain Pencahayaan Berbasis Eksistansi Permukaan Ruang Rata-rata pada Kasus Kamar Tamu Premium Hotel - Mangkuto, Rizki Armanto; Azzami, Muhammad Rafi; Sugihartadi, Re Rakannabyan (Nature: National Academic Journal of Architecture, 2024)
The current interior lighting design concept has adopted the concept of mean room surface exitance (MRSE), which is important to the emphasize on the perceptual brightness or ambient illuminance of the space as a whole, instead of using the workplane illuminance parameter, which is often inefficient in terms of energy use. An application of lighting design that requires specific attention is hotel guestrooms, which shall provide comfort and aesthetics, and shall accomodate various visual activities of the occupants. The purpose of this study is to apply the concept of MRSE-based electric lighting design to the case of a premium hotel guestroom, to improve visual comfort and energy efficiency. The implemented method is determining the target/ambient illuminance ratio (TAIR) for each object in the room, determining the amount of luminous flux that must be provided, and determining the MRSE and TAIR values from the lighting simulations using DIALux evo software in various scenarios, namely in the (1) bathroom, (2) main (bed)room for reading and writing, (3) main room for sleeping, and (4) main room for reading prior to sleeping. Initial design calculation indicates MRSE values of 100 lm/m2 in Scenario 1, 100 lm/m2 in Scenario 2, 30 lm/m2 in Scenario 3, and 30 lm/m2 in Scenario 4. The simulation results show that the MRSE value from the modeling is found to be 147.5 lm/m2 1, 109.5 lm/m2, 30.2 lm/m2, and 32.5 lm/m2 in each scenario, in relatively close agreement with the initial design calculations, satisying the visual comfort target and increasing the efficiency of electric lighting energy use. This study contribute in demonstrating the interior lighting design concept that can be correlated with the perceptual brightness of the occupants, as well as with the energy efficiency improvement.